2019
DOI: 10.3389/fonc.2019.00698
|View full text |Cite
|
Sign up to set email alerts
|

Precision Medicine Tools to Guide Therapy and Monitor Response to Treatment in a HER-2+ Gastric Cancer Patient: Case Report

Abstract: Trastuzumab, has played a major role in improving treatment outcomes in HER-2 positive gastric cancer. However, once there is disease progression there is a paucity of evidence for second line therapy. Patient-derived xenografts (PDXs) in combination with liquid biopsies can help guide individual therapeutic decisions and have now started to be studied. In the present case we established a PDX model from a metastatic HER-2+ gastric cancer patient and after the first engraftment passage we performed a mouse cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 33 publications
(31 reference statements)
0
5
0
Order By: Relevance
“…Improving technologies have enabled a more comprehensive molecular analysis in the body fluids of patients with cancer and have revealed that circulating tumor-derived molecules could provide multilayer molecular information suitable for cancer diagnostics, prognosis, or even response to therapy (6)(7)(8). The currently available studies analyzing ctDNA alterations in GC focus on a limited number of well-known oncogenes such as TP53 (6) and HER2 (9)(10)(11). On the other hand, studies implementing high-throughput technologies such as new generation sequencing (NGS) are still very scarce and have been mostly conducted in Asian populations (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…Improving technologies have enabled a more comprehensive molecular analysis in the body fluids of patients with cancer and have revealed that circulating tumor-derived molecules could provide multilayer molecular information suitable for cancer diagnostics, prognosis, or even response to therapy (6)(7)(8). The currently available studies analyzing ctDNA alterations in GC focus on a limited number of well-known oncogenes such as TP53 (6) and HER2 (9)(10)(11). On the other hand, studies implementing high-throughput technologies such as new generation sequencing (NGS) are still very scarce and have been mostly conducted in Asian populations (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…Although still few, some fundamental studies in mice were performed in a prospective manner to guide clinical treatment decisions [76,[94][95][96][97]. In 2014, Stebbing et al [95] established 16 mPDXs from 29 patients with advanced sarcoma.…”
Section: Correlation Of Drug Response With Matched Patient Treatment mentioning
confidence: 99%
“…Despite limitations in efficiency, speed and cost, Avatars proved to be useful at tailoring therapy in 5 patients [95]. More recently, Mahecha and colleagues established a mPDX model from a metastatic HER2 + gastric cancer patient and tested ado-trastuzumab emtansine as an alternative therapy for the patient, who responded to treatment before relapsing 6 months later [97]. Results from mouse Avatars generally take months to be available.…”
Section: Correlation Of Drug Response With Matched Patient Treatment mentioning
confidence: 99%
“…ctDNA can be used for HER2-targeted population screening, since there is a high concordance of HER2 amplification between ctDNA and tumor tissues ( 52 , 53 ). Also, HER2 CNV detected in ctDNA could be used to monitor trastuzumab efficacy ( 52 , 54 , 55 ), as well as to predict innate trastuzumab resistance ( 54 ) and the developed one ( 43 ).…”
Section: Clinical Utility Of Ctdnamentioning
confidence: 99%